Inclusive growth and education: on the approach to the eleventh plan - Tilak, Jandhyala B.G. (2007)
Inclusive growth is regarded as the new mantra of development. This paper critically looks at the approach to the development of education outlined in the Approach to the Eleventh Five-Year Plan, some of the new and not-so-new strategies proposed, a few controversial proposals, the assumptions that underlie them, the issues conveniently ignored and highlights the weaknesses and the continuation of the big policy vacuum. - Reproduced.
Keywords: Eleventh plan; Education - India; Economic growth - India; Economic growth